PERANAN KANTOR PELAYANAN PAJAK PRATAMA (KPPP) PEKANBARU TAMPAN DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DALAM MEMBAYAR PAJAK - Niken Sekarwati; Erman M. " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine the participation of the community to paying taxes 2015, knowing the role of the tax at KPP Pekanbaru Tampan ini paying taxis at 2015 This research conducted at the KPP Pratama Pekanbaru Tampan is located at Jln Arengka Ring Road II (Jln SM Amin), Pekanbaru. The source data of this study is the informant on KPP Pekanbaru Tampan, particularly data regarding the role of the community in paying taxes, the efforts and factors that inhibiting participation in paying taxes. The informanta are all employees at the KPP Pekanbaru Tampan. Analysis data using qualitative descriptive approach. The study states that the KPPP Pekanbaru Tampan improve community participation to pay taxes to have some role or business include: providing extension, hold services of tax consultancy, dissemination of information on tax and publishing book of tax, mass media, through campaign with the distribution of brochures and souvenirs to the public (tax payer), and provide a drop box. Factors that inhibit the KPPP Pekanbaru Tampan in improving community participation to pay taxes such as: a) the quality of service. This factor is the lack of front-liner, b) The originating factors from outside, this factor is a system that is too difficult to understand and not up to date.Keywords : Participation, People, Taxes